2016
DOI: 10.1038/leu.2016.274
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of 6-month maintenance chemotherapy for acute lymphoblastic leukemia in children

Abstract: In the treatment of childhood acute lymphoblastic leukemia (ALL), excess shortening of maintenance therapy resulted in high relapse rate, as shown by our previous trial, TCCSG L92-13, in which maintenance therapy was terminated at 1 year from initiation of treatment. In this study, we aimed to confirm the long-term outcome of L92-13, and to identify who can or cannot be cured by shorter duration of maintenance therapy. To obtain sentinel cytogenetics information that had been missed before, we performed geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 24 publications
2
32
1
Order By: Relevance
“…Unexpectedly, TCF3-PBX1 patients, an intermediate-risk abnormality, demonstrated an even faster MRD clearance, with 43% achieving MRD negativity ( Fig 2 ) compared with 36% of ETV6-RUNX1 patients. These observations correlate with the recent report from the TCCSG L92-13 trial 28 that showed that ETV6-RUNX1 and TCF3-PBX1 patients had an excellent outcome despite receiving less maintenance therapy. Thus, a greater understanding of disease kinetics could help tailor treatments to different subtypes.…”
Section: Discussionsupporting
confidence: 90%
“…Unexpectedly, TCF3-PBX1 patients, an intermediate-risk abnormality, demonstrated an even faster MRD clearance, with 43% achieving MRD negativity ( Fig 2 ) compared with 36% of ETV6-RUNX1 patients. These observations correlate with the recent report from the TCCSG L92-13 trial 28 that showed that ETV6-RUNX1 and TCF3-PBX1 patients had an excellent outcome despite receiving less maintenance therapy. Thus, a greater understanding of disease kinetics could help tailor treatments to different subtypes.…”
Section: Discussionsupporting
confidence: 90%
“…In childhood ALL, TEL‐AML1 fusion gene is related to favorable outcome. Studies on TEL‐AML1 positive groups in different treatment protocols have shown EFS around 90%, at 5 to 10 years during follow‐up . In the present study ( n = 62), EFS at 7 years from diagnosis was 87.0% ± 4.3%, which was close to the results of Enshaei et al (81%) …”
Section: Discussionsupporting
confidence: 88%
“…A UK group showed that 20% of deaths resulting from infection occurred during maintenance therapy, and a Scandinavian group demonstrated that a longer duration of maintenance therapy and a higher dose of 6‐MP increased the risk of secondary malignancy . In view of these adverse events, the TCCSG re‐analyzed their anecdotal evidence from the L92‐13 study with additional genomic analysis and found that female patients with TCF3‐PBX1 or ETV6‐RUNX1 had favorable outcomes even when maintenance therapy was terminated early, while full duration of maintenance therapy was required for male patients, and patients with HHD …”
Section: Treatmentmentioning
confidence: 99%
“…51 In view of these adverse events, the TCCSG re-analyzed their anecdotal evidence from the L92-13 study with additional genomic analysis and found that female patients with TCF3-PBX1 or ETV6-RUNX1 had favorable outcomes even when maintenance therapy was terminated early, while full duration of maintenance therapy was required for male patients, and patients with HHD. 52 In previous trials, treatment stratification generally consisted of intensification or reduction according to the relapse risk. For further improvement, however, the duration of therapy may also be optimized based on the patient characteristics ( Fig.…”
Section: Maintenance Therapymentioning
confidence: 99%